2004
DOI: 10.1086/383567
|View full text |Cite
|
Sign up to set email alerts
|

On the Black Hole Mass-Bulge Mass Relation

Abstract: We have re-examined the relation between the mass of the central black holes in nearby galaxies, M bh , and the stellar mass of the surrounding spheroid or bulge, M bulge . For a total of 30 galaxies bulge masses were derived through Jeans equation modeling or adopted from dynamical models in the literature. In stellar mass-to-light ratios the spheroids and bulges span a range of a factor of eight. The bulge masses were related to well-determined black hole masses taken from the literature. With these improved… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

174
1,931
13
5

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,604 publications
(2,135 citation statements)
references
References 46 publications
174
1,931
13
5
Order By: Relevance
“…At least out to a redshift of three, the overall evolution in the rates of starformation and black hole accretion track one another rather well: a steep rise by about an order-of-magnitude from z = 0 to 1 and then relatively little change between z = 1 to 3 (e.g., Marconi et al 2004). Coupled with the tight correlation between the mass of the black hole and the velocity dispersion and mass of the galactic bulge within which it resides (e.g., Gultekin et al 2009;Marconi & Hunt 2003;Haring & Rix 2004), there is 4 T. M. Heckman then compelling evidence for a close connection between the formation of the black hole and that of its host galaxy (e.g., Kauffmann & Haehnelt 2000;Granato et al 2001).…”
Section: Introductionmentioning
confidence: 86%
“…At least out to a redshift of three, the overall evolution in the rates of starformation and black hole accretion track one another rather well: a steep rise by about an order-of-magnitude from z = 0 to 1 and then relatively little change between z = 1 to 3 (e.g., Marconi et al 2004). Coupled with the tight correlation between the mass of the black hole and the velocity dispersion and mass of the galactic bulge within which it resides (e.g., Gultekin et al 2009;Marconi & Hunt 2003;Haring & Rix 2004), there is 4 T. M. Heckman then compelling evidence for a close connection between the formation of the black hole and that of its host galaxy (e.g., Kauffmann & Haehnelt 2000;Granato et al 2001).…”
Section: Introductionmentioning
confidence: 86%
“…This figure is reproduced from Alexander et al (2008) with permission from the authors and AAS. The local relationship is given by the dashed line (Häring & Rix, 2004), whereas the measurement for radio-selected AGN between 0 < z < 2 is shown in dark gray (McLure et al, 2006) and z > 2 quasars in light gray (Peng et al, 2006). Also overplotted are measurements of local obscured ULIRGs (Veilleux et al, 1997(Veilleux et al, , 1999.…”
Section: Agn Contentmentioning
confidence: 99%
“…Alexander et al place observational constraints on central black-hole masses for SMGs using Hα (or Hβ) line analysis in addition to the X-rays. They find that SMGs have black-hole masses to galaxy mass ratios 3-5× lower than local relationship (Häring & Rix, 2004), and much lower than other high-redshift populations of AGN (McLure et al, 2006;Peng et al, 2006). A summary of results regarding X-ray studies of SMGs and their AGN is summarized in Figure 27.…”
Section: Agn Contentmentioning
confidence: 99%
“…The dashed line denotes the observational estimate by Häring & Rix (2004) for a local sample of galaxies. For BH masses above ∼ 5 × 10 6 M , the simulated and observed relations agree very well, indicating that possibly not too much evolution is expected in this relation from z = 1 to z = 0.…”
Section: Impact Of Agn Feedback On Galaxy Formationmentioning
confidence: 99%
“…Recent observational findings (e.g., Tremaine et al 2002;Häring & Rix 2004) have shown that BHs are tightly linked to the properties of their host galaxies. From a theoretical standpoint it is still unclear why a relationship between BHs and galaxy bulges should exist or how it evolves with redshift.…”
Section: Introductionmentioning
confidence: 99%